Staged surgical management of hypoplastic left heart syndrome: a single institution 12 year experience. Issue 3 (6th June 2005) - McGuirk, S P; Griselli, M; Stumper, O F; Rumball, E M; Miller, P; Dhillon, R; de Giovanni, J V; Wright, J G; Barron, D J; Brawn, W J
Abstract : Objective: To describe a 12 year experience with staged surgical management of the hypoplastic left heart syndrome (HLHS) and to identify the factors that influenced outcome. Methods: Between December 1992 and June 2004, 333 patients with HLHS underwent a Norwood procedure (median age 4 days, range 0–217 days). Subsequently 203 patients underwent a bidirectional Glenn procedure (stage II) and 81 patients underwent a modified Fontan procedure (stage III). Follow up was complete (median interval 3.7 years, range 32 days to 11.3 years). Results: Early mortality after the Norwood procedure was 29% (n  =  95); this decreased from 46% (first year) to 16% (last year; p < 0.05). Between stages, 49 patients died, 27 before stage II and 22 between stages II and III. There were one early and three late deaths after stage III. Actuarial survival (SEM) was 58% (3%) at one year and 50% (3%) at five and 10 years. On multivariable analysis, five factors influenced early mortality after the Norwood procedure (p < 0.05). Pulmonary blood flow supplied by a right ventricle to pulmonary artery (RV-PA) conduit, arch reconstruction with pulmonary homograft patch, and increased operative weight improved early mortality. Increased periods of cardiopulmonary bypass and deep hypothermic circulatory arrest increased early mortality. Similar factors also influenced actuarial survival after the Norwood procedure. Conclusion: This study identified an improvement in outcome after staged surgical management of HLHS, which was primarily attributable to changes in surgical technique. The RV-PA conduit, in particular, was associated with a notable and independent improvement in early and actuarial survival.